New modification on feistel DES algorithm based on multi-level keys - Suhad M. Kareem; Abdul Monem S. Rahma (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The data encryption standard (DES) is one of the most common symmetric encryption algorithms, but it experiences many problems. For example, it uses only one function (XOR) in the encryption process, and the combination of data is finite because it occurs only twice and operates on bits. This paper presents a new modification of the DES to overcome these problems. This could be done through adding a new level of security by increasing the key space (using three keys) during the 16 rounds of the standard encryption algorithm and by replacing the predefined XOR operation with a new # operation. Our proposed algorithm uses three keys instead of one. The first key is the input key used for encrypting and decrypting operations. The second key is used for determining the number of bits, while the third key is used for determining the table numbers, which are from 0 to 255. Having evaluated the complexity of our proposed algorithm, the results show that it is the most complex compared with the well-known DES and other modified algorithms. Consequently, in our proposed algorithm, the attacker try a number of attempts 21173 at minimum to decrypt the message. This means that the proposed DES algorithm will increase the security level of the well-known DES.